Clinicopathological analysis of PD-L1 and PD-L2 expression in pulmonary squamous cell carcinoma: Comparison with tumor-infiltrating T cells and the status of oncogenic drivers. Issue 1 (April 2015) - Kim, Moon-Young; Koh, Jaemoon; Kim, Sehui; Go, Heounjeong; Jeon, Yoon Kyung; Chung, Doo Hyun
Highlights We examine PD-L1, L2 expression and PD-1+, CD8+ cell in lung squamous cell carcinoma. PD-L1 and L2 are expressed in approximately one-fourth of patients. PD-L1 expression is significantly and consistently related with increased CD8+ cell. MET expression is correlated with PD-L2 expression and increased PD-1+ cells. This provides rationale for anti-PD-1/PD-L1 immunotherapy in squamous cell carcinoma.